Abuse of forward contracts to semi-collude in volatile markets - Markus Aichele (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
I model the optimal semi-collusive strategy of firms using forward contracts in volatile markets. It has been shown that forward contracts can be used to stabilize a collusive agreement under deterministic (Liski and Montero, 2006) as well as under stochastic market conditions (Aichele, 2012). However, forward trading has a negative effect on the expected profit for collusive firms, since firms have the obligation to fulfill their forward contracts in booms as well as in recessions. Thus, in recessions firms involuntarily sell more than the optimal collusive amount. This profit decreasing effect of forward trading is in contrast to the existing literature, since under certainty forward trading does not alter the collusive profit.
Keywords: L13; D43; K21; 330